TNF-α and LT-α Polymorphisms and the Risk of Leukemia: A Meta-analysis. Issue 1 (January 2017) - Gong, Li-li; Han, Fei-fei; Lv, Ya-li; Liu, He; Wan, Zi-rui; Zhang, Wen; Shi, Ming-biao; Pei, Li-xia; Liu, Li-hong
Aim: The aim of this study is to investigate whether TNF-α or LT-α polymorphisms are associated with the risk of leukemia. Methods: A meta-analysis was performed to examine the association between the TNF-α −308 G>A and LT-α +252 A>G polymorphisms and the incidence of leukemia. We also performed subgroup analyses based on the classification of leukemias. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to evaluate the association. Results: A total of 19 publications comprising 1, 509 cases and 4, 075 controls were selected in the study. An association between the risk of leukemia and the LT-α +252 AA genotype was found (GG + AG vs. AA, OR = 0.485, 95% CI 0.368-0.639, p = 0.000). After multivariable analysis TNF-α polymorphism showed no consistent association with leukemia. Conclusions: This meta-analysis suggests that the LT-α +252 AA polymorphism is associated with the risk of leukemia.